Evaluation of the Society of Thoracic Surgeons score system for isolated coronary bypass graft surgery in a Brazilian population - Dimas Tadahiro Ikeoka; Viviane Aparecida Fernandes; Otavio Gebara; Jose Carlos Teixeira Garcia; Pedro Gabriel Melo de Barros e Silva; Marcelo Jamus Rodrigues; Valter Furlan; Antonio Claudio do Amaral Baruzzi (Brazilian Journal of Cardiovascular Surgery, 2014)
Objective: Report the experience with the Society of Thoracic Surgeons scoring system in a Brazilian population submitted to isolated coronary artery bypass graft surgery. Methods: Data were collected from January-2010 to December-2011, and analyzed to determine the performance of the Society of Thoracic Surgeons scoring system on the determination of postoperative mortality and morbidity, using the method of the receiver operating characteristic curve as well as the Hosmer-Lemeshow and the Chi-square goodness of fit tests. From the 1083 cardiac surgeries performed during the study period 659 represented coronary artery bypass graft procedures which are included in the present analysis. Mean age was 61.4 years and 77% were men. Results: Goodness of fit tests have shown good calibration indexes both for mortality (X2=6.78, P=0.56) and general morbidity (X2=6.69, P=0.57). Analysis of area under the ROC-curve (AUC) demonstrated a good performance to detect the risk of death (AUC 0.76; P<0.001), renal failure (AUC 0.79; P<0.001), prolonged ventilation (AUC 0.80; P<0.001), reoperation (AUC 0.76; P<0.001) and major morbidity (AUC 0.75; P<0.001) which represents the combination of the assessed postoperative complications. STS scoring system did not present comparable results for short term hospital stay, prolonged length of hospital stay and could not be properly tested for stroke and wound infection. Conclusion: Society of Thoracic Surgeons scoring system presented a good calibration and discrimination in our population to predict postoperative mortality and the majority of the harmful events following coronary artery bypass graft surgery. Analysis of larger samples might be needed to further validate the use of the score system in Brazilian populations.